Studi al-Qur’an : Kajian al Qur’an dalam Menyikapi Munculnya Aliran-aliran pada Golongan Ahlussunnah wal Jama’ah - Abd Quddus Al-Badani (AS-SABIQUN, 2019)
Al-Qur'an study is a study that is needed in this millennial era, because various types of streams that appear endless are caused by a lack of understanding of the Qur'an itself. The emergence of these schools on the basis of the interpretation of the Qur'an textually without considering the current conditions. In addition, the interpretation of the Qur'an is carried out without sufficient scientific basis. This study of the Qur'an aims to provide understanding to all who need to interpret the Qur'an. With these discussions, it can help to prevent textual interpretations of the Qur'an from happening again, but it can open up insights in interpreting the Qur'an contextually. Because the times are so in need of a foundation in acting and behaving.